The influence of fashion involvement, hedonic consumption, and visual merchandising on impulse buying with positive emotion as mediation variables - Setyawati, Sri Murni; Sumarsono, Sumarsono; Praditya, Intan (Faculty of Economics and Business, Jenderal Soedirman University, 2018)
This research aims to analyze the influence of fashion involvement, hedonic consumptions, and virtual merchandising on impulse buying with positive emotion as mediator variable at Popies Girls Shop. The population of this study was the female students of Economics and Business Faculty, Jenderal Soedirman University. The researcher used 145 samples. Sampling technique used in this research was random sampling. Data were analyzed using Structural Equation Modeling (SEM). The result of this research analysis shows that: (1) the involvement of fashion had a positive effect on positive emotion, (2) the trend of hedonic consumption did not have effect on positive emotion, (3) visual merchandising had positive effect on positive emotion, (4) positive emotion had positive effect on impulse buying, (5) positive emotion mediates the relationship between involvement fashion and impulse buying, (6) positive emotion does not mediate the relationship between trends in hedonic consumption and impulse buying, (7) positive emotion mediates the relationship between the visual merchandising and impulse buying.